KARAKTERISTIK DEMOGRAFI DAN TINGKAT PENDAPATAN PEMULUNG DI TPA JATIBARANG KOTA SEMARANG - Sriyono Sriyono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
The aim of this research was to discover the trash collection activities, especially in TPAJatibarang, Semarang City, which includes the demographic characteristics and their relations to the level ann factors in cho.osing the profession. The research population which amount reaches for 250 persons. But we only took 31 respondent as samples. Investigated variables include the demographic characteristics, income level. and fac• tors in choosing the trash collectors as their profession. The interview uses the instrument of inter• view guide that was used to collect the data. While the data analysis use the percentage descriptive analysis and cross-tabulation.The results indicate that most (70,97 %) of trash collectors in TPA Jatibarang are men, at the age of 35 and older (67,74%), have marital status (74,32%) come from another cities. and their educational background are the from elementary school (77,42% ), and they do not have and may be they do not need any transportation devices because they live arround the TPA (they made plain huts). The related factors between the demographic characteristics and the productivities of trash collec• tors are the facts the visitors of the community have more work hours (>6 hours a day), so it increases their income (Rp. 75.000-Rp. 100.000); even more). While factors that motivate them to be trash collectors are the decreasing of work land (for ex-farmer), the decreasing of job field and responbilities to gain more income for their family needs. As the encouraging factors, commonly they said that this kind of proffesion does not require any special skill and capital, free nor have no rule and boundaries. Base on the results, we can conclude that: there are variations in demographic characteristics of trash collectors, the average income level is between Rp. 75.000- Rp. I 00.000 a week; the trash collectors in the age 35 or older and came from another cities have higher productivity; and the decreasing fof work land and job fields, and theirresponbilies to their family become the motivator to be trash collectors, while the incouraging factors are the facts that no special skill and capitals needed, and also, there are no rule and time boundaries. To improve the live quality of trash collectors, we suggest that the goverrnent and any competent privte institutions should show that they care for the community by giving them organization and management guidence, and residental and health facilities.